Impact of Benzene Exposure on The Hematological Parameters of Workers Fuel Stations in Thi-Qar Province - Salah Faiz Shnaa,; Majida Ghazi Magtooph, (University of Thi-Qar Journal of Science, 2021)
Benzene is one of the most toxic chemicals, it is very effective and causes widespread health problems for humans. Workers of stations are directly exposed to inhalation of a large amount of steam that is discharged from the tank into their breathing zone; causing to hematological toxicity. The danger of exposure to benzene lead to a negative and dangerous effect on human health. This study was designed to find out the negative impact of gasoline on the health of workers at gas stations of Nasiriyah city. The current study has included the collection of 90 male samples consisting of (60 samples from gas stations workers, and 30 samples from healthy people, far from any direct source of exposure to benzene as a control group). After that, a complete analysis of the blood image was performed using a whole hematology analyzer (Coulter) and The estimation of Lead (Pb) Concentration in serum by Flame Atomic Absorption Spectrometer (FAAS) of the workers and control groups. The results of current study showed According to age group : Workers had higher level of Hemoglobin (Hb), Hematocrit (HCT) and higher count of Monocyte (MONO), Red blood cells (RBC) and had lower counts of granulocytes (GRAN) compared to the control group. According to smoking status Smokers have high levels of Hemoglobin (Hb) , Hematocrit (HCT) and high counts of Monocyte (MONO), Red blood cells (RBC) and Lymphocyte. While Platelet (PLT), Mean Platelet Volume (MPV), White blood cells (WBCs), and granulocytes (GRAN) counts decreased when compared to the control group. The study have not found significant differences with the rest of the blood parameters. The lead concentration also increases in the blood serum of fuel station workers increases with increasing age and increases in smoking workers.